Assessment of radiation exposure and public health before and after the operation of Sanmen nuclear power plant - Ren, Hong; Yu, Shunfei; Wang, Ziyou; Zheng, Taotao; Zou, Hua; Lou, Xiaoming; Wang, Peng; Zhou, Lei; Zhang, Dongxia; Zhang, Meibian; Guo, Jiadi; Lai, Zhongjun; et al. (Frontiers in Public Health, 2023)
Sanmen nuclear power plant (SNPP) operates the first advanced passive (AP1000) nuclear power unit in China. To assess the radiological impacts of SNPP operation on the surrounding environment and the public health, annual effective dose (AED) and excess risk (ER) were estimated based on continuous radioactivity monitoring in drinking water and ambient dose before and after its operation during 2014-2021. In addition, the residents’ cancer incidence was further analysed through authorized health data collection. The results showed that the gross α and gross β radioactivity in all types of drinking water were ranged from 0.008 to 0.017 Bq/L and 0.032 to 0.112 Bq/L, respectively. The cumulative ambient dose in Sanmen county ranged from 0.254 to 0.460 mSv/y, with an average of 0.354 ± 0.075 mSv/y. There is no statistical difference in drinking water radioactivity and ambient dose before and after the operation of SNPP according to Mann-Whitney U test. The Mann-Kendall test also indicates there is neither increasing nor decreasing trend during the period from 2014 to 2021. The age-dependent annual effective doses due to the ingestion of drinking water or exposure to the outdoor ambient environment are lower than the recommended threshold of 0.1 mSv/y, indicating negligible radiological risk for the local public around the SNPP. The incidence of cancer (include leukemia and thyroid cancer) in the population around SNPP is slightly higher than that in other areas, while it is still in a stable state characterized by annual percentage changes.